KEBIJAKAN TATA RUANG DI KABUPATEN KUTAI KARTANEGARA (STUDI VALORISASI RUANG) - Subekti, Rahayu; Karjoko, Lego; Astuti, Wida (Yustisia, 2013)
AbstractThe objective of research was to find out the existing condition of spatial layout the Kutai Kartanegara Regency’s Government used and to find out the policy of Kutai Kartanegara Regency’s Government in spatial layout. In this research, Empirical research on Law (ELr) was used. ELr seeks to understand and explain how law works in the real world. This study was a descriptive developmental one providing a systematical description on the object to be studied, and then a model was developed to address the problems in the field. The research approach used was qualitative approach. The research was taken place in Kutai Kartanegara regency. From the result of research and discussion, two conclusions could be drawn. Firstly, the existing condition of land use in Kutai Kartanegara regency showed the land use for various activities such as: mining, forestry, gardening, and farming. The shift of land function increased over years. Secondly, the government of Kutai Kartanegara regency had developed draft Local regulation of regency about rTrW or Zoning for Kutai Kartanegara regency, but it had not been proposed to the Local Legislative Assembly’s (dprd’s) discussion because there had been no provincial regulation about rTrW or Zoning of East Kalimantan provinceKey words : policy, Special layout, ValorisationAbstrakTujuan penelitian adalah untuk mengetahui existing condition tata ruang yang digunakan Kabupaten Kutai Kartanegara, untuk mengetahui kebijakan Pemerintah Kabupaten Kutai Negara dalam penataan ruang. Dalam penelitian ini digunakan metode Empirical research on Law (ELr). ELr seeks to understand and explain how law works in the real world. Adapun sifat penelitiannya deskriptif developmental yang memberikan gambaran secara sistematis terhadap obyek yang akan diteliti, selanjutnya disusun model yang dapat dikembangkan untuk mengatasi problema di lapangan. Pendekatan penelitian menggunakan pendekatan kualitatif. Lokasi penelitian meliputi Kabupaten Kutai Kartanegara. Dari Hasil penelitian dan pembahasan dihasilkan dua kesimpulan, yaitu : pertama, Kondisi existing Penggunaan tanah di Kabupaten Kutai Kartanegara untuk bermacam – macam kegiatan diantaranya yaitu : . Kegiatan  pertambangan  , Kegiatan Kehutanan , Kegiatan Perkebunan, kegiatan pertanian. Terjadi pengalihan fungsi lahan yang meningkat dari tahun ketahun Kedua, Pemerintah Kabupaten Kutai Kartanegara telah membuat Draft Rancangan Peraturan Daerah Kabupaten Tentang RTRW maupun Zonasi Kabupaten Kutai Kertanegara, hanya saja belum bisa diajukan dalam pembahasan dengan DPRD karena Peraturan Daerah Propinsi tentang RTRW maupun zonasi Provinsi Kalimantan Timur belum ada.Kata kunci : Kebijakan, tata ruang, valorisasi